Answer: -23
Step-by-step explanation:
Answer:
false
Step-by-step explanation:
an integer is any number greater or less than 0
Answer: So True
Step-by-step explanation:
Answer:
= (3t+2)(3t-2)(3t-4)
Step-by-step explanation:
Given the expression 27t^3 - 36t^2 - 12t + 16
On factoring:
(27t^3 - 36t^2) - (12t + 16)
= 9t²(3t-4)-4(3t-4)
= (9t²-4)(3t-4)
factoring 9t²-4
9t²-4 = (3t)² - 2²
From different of two square, a²-b² = (a+b)(a-b)
Hence (3t)² - 2² = (3t+2)(3t-2)
= (9t²-4)(3t-4)
= (3t+2)(3t-2)(3t-4)
Hence the factored form of the expression is (3t+2)(3t-2)(3t-4)